Punching shear behaviour of ultra high strength flat slabs using alternative techniques of shear reinforcement - Mohamed Fawzy Nail Ibrahim; Walid Abdel Latif Attia; Sherif Kamal Al-Din Elwan (2025)
This research consists of a numerical analysis using a finite element software program (ANSYS) using four groups of 20 specimens. The first group deals with some of the specimens from research experimental work NSC with shear reinforcement techniques, which are shear heads, shear bolts, and stirrups and also UHSC without shear reinforcement to verify it. The second group of specimens was made to investigate the influence of using shear head reinforcement in enhancing the punching shear capacity of UHSC flat slabs and also to Evaluate the effect of length for steel shear head arm on the improvement of the punching shear strength of UHSC flat slabs. The third group of specimens was made to investigate the influence of using shear bolt reinforcement in enhancing the punching shear capacity of UHSC flat slabs and also to evaluate the effect of steel shear bolt spacing and the number of bolts in a row on the improvement of the punching shear strength of UHSC flat slabs. The fourth group of specimens was made to investigate the influence of using stirrups in enhancing the punching shear capacity of UHSC flat slabs and also to Evaluate the effect of the number of stirrup branches and spacing between stirrups on the improvement of the punching shear strength of UHSC flat slabs.
(3jgOa GdHMK Gdi OQGSI Sdhc GdHdGWGJ GdNQSGfjI GdeSWMI aGFbI GdebGheI JMJ JGKjQ GdbU GdKGbH HGSJNOGe JbfjGJ HOjdI ef MOjO GdbU(B. (3jJchf gPG GdHMK jJchf gPG GdHMK ef JMdjd YOOj HGSJNOGe HQfGeL GdYfGUQ GdeMOhOI (B(ANSYS) (3ef (B4 (3eLehYGJ ef (B20 (3YjfI(B. (3JJfGhd GdeLehYI GdChdi HYV GdYjfGJ ef CHMGK GdYed GdJLQjHj dd`NQSGfI YGOjI GdebGheI (B(NSC) (3eY JbfjGJ MOjO GdbU hgj QDhS GdbU heSGejQ GdbU hGdcGfGJ hCjVG Gd`NQSGfI aGFbI GdebGheI (B(UHSC) (3HOhf MOjO GdbU ddJMbb ef GdeMGcGI(B. (3Je Yed GdeLehYI GdKGfjI ef GdYjfGJ ddJMbjb aj JCKjQ GSJNOGe JbhjI QCS GdbU aj JYRjR bOQI bU GdKGbH ddHdGWGJ GdeSWMI Gd` (BUHSC (3hCjVG dJbjje JCKjQ GdWhd dPQGY QCS GdbU GdahdGPj Ydi JMSjf ebGheI bU GdKGbH(B. (3Je Yed GdeLehYI GdKGdKI ef GdYjfGJ ddJMbjb aj JCKjQ GSJNOGe JbhjI eSGejQ GdbU aj JYRjR bOQI GdbU GdKGbH ddHdGWGJ GdeSWMI Gd` (BUHSC (3hCjVG dJbjje JCKjQ JHGYO eSGejQ GdbU GdahdGPjI hYOO GdeSGejQ Ydi JMSjf ebGheI GdbU GdKGbH (B. (3Je Yed GdeLehYI GdQGHYI ef GdYjfGJ dOQGSI JCKjQ GSJNOGe GdcGfGJ aj JYRjR bOQI GdbU GdKGbH ddHdGWGJ GdeSWMI Gd` (BUHSC (3hCjVG dJbjje JCKjQ YOO aQhY GdcGfGJ hGdJHGYO Hjf GdcGfGJ Ydi JMSjf ebGheI GdbU GdKGbH (B.s
Thesis (M.Sc.)-Cairo University, 2025.
Bibliography: pages 234-238.
Issues also as CD.
Text in English and abstract in Arabic & English.
Keywords: Structural Engineering; (3GdgfOSI GdEfTGFjIs; Punching -- Ultra High Strength -- Shear Reinforcement -- Shear Head -- Shear Bolt